Potensi Bahan Pengencer Citrat dan Kuning Telur yang Berbeda Rasio Terhadap Kualitas Spermatozoa Ayam Kampung - Abdul Malik (Universitas Muhammadiyah Purworejo, 2018)
This study emphasizes the importance of citric diluents with egg yolks and storage time for semen quality of native chickens. Semen is accommodated using the abdominal back massage method in male chickens. The parameters studied in this research are viability. After being collected semen is evaluated then diluted with citrate and egg yolk by setting P0 (1: 1) as a control, P1 (1: 2), P2 (1: 3) and P3 (1: 4) which are then displayed indoors with long 0 minutes (control), 45 minutes, 90 minutes and 135 minutes. The results showed that the diluent of citrate and egg yolk stored for 90 minutes at the time of P1 treatment had a marked decrease in viability (P <0.05) compared to P0 training (control) but when compared with P2 assistance the results turned out to be unreal (P> 0.05) but there is a trend of increasing viability in the storage.